A nanobody-derived mimotope against VEGF inhibits cancer angiogenesis. (1st January 2020) - Karami, Elmira; Sabatier, Jean-Marc; Behdani, Mahdi; Irani, Shiva; Kazemi-Lomedasht, Fatemeh
Abstract: Vascular Endothelial Growth Factor (VEGF) promotes angiogenesis in tumours of various cancers. Monoclonal antibodies and nanobodies are one of the potent agents in the treatment of cancer. Due to their high costs, researchers are considering to design and produce peptides as a substitute approach in recent years. The aim of the current study was designing a mimotope against VEGF and evaluate its effects on cell proliferation and tube formation in the HUVEC cell line. For this, a peptide was designed against VEGF and chemically produced. The effects of synthetic peptide and nanobody on the inhibition of proliferation of HUVEC cells were examined using MTT and tube formation assays. The data indicate that the peptide was able to significantly inhibit both HUVEC cell proliferation and tube formation through inhibition of VEGF, highlighting the potential of peptides as a 'novel' class of candidate drugs to inhibit angiogenesis.